Competitiveness of Fruit Exporter Firms in Mexico: An Econometric Analysis - Alma L. ORTIZ; Mario GÓMEZ; José Carlos RODRÍGUEZ (Communications of International Proceedings, 2021)
The purpose of this article is to study the effect of supply chain management (SCM), supply chain responsiveness (SCR), and human resource management (HRM) on the competitive advantage of fruit exporting companies in Michoacán, Mexico. The data was collected through a census of 61 companies belonging to the fruit sector in 2018. Descriptive statistics were used for data analysis, and a multiple regression model was applied. The results suggest that the relationship with strategic suppliers, the responsiveness of logistics processes, and training and skills development practices positively affect the companies' competitiveness under study. Including suppliers in the company's processes, building long-term relationships with them, implementing transportation practices, distribution and storage to quickly respond to unexpected changes in demand, and adequately managing human resources may contribute to developing a competitive advantage.
Keywords: Econometric Model; Competitive Advantage; Human Resource Management; Supply Chain Management.